CARI MONTIR Ltd. “Vehicle Service Application” - Restu Aprilianto; Unggul Kustiawan (Syntax Corporation Indonesia, 2023)
The high number of motorized vehicle population in Indonesia makes the potential need for motor vehicle services high. The high number of motorized vehicle users reflects the very dense activity of the community, increase to the need for facilities that can simplify and cut time for servicing motorized vehicles that are supported by existing information systems. The potential need for motorcycle service and the development of information systems is the background for Carimontir to create technology based on motor vehicle service applications. With this application, it can make it easier for motorized vehicle owners to carry out vehicle service more quickly and practically anytime and anywhere, while for partners, it will be easier to reach potential consumers. Carimontir has an IFE value of 3.04 and EFE value of 3.03, where its competitive strength is at the medium level based on the results of Porters 5 Forces analysis. The Carimontir Strategic Plan based on the IE Matrix is ??in the growth and build cell. Based on the SWOT and QSPM analysis, Carimontir chose social media marketing optimization strategy and feature innovation. Meanwhile, based on the porter's generic strategy, Carimontir chose a differentiation strategy in order to be competitive and sustainable in the service provider application business. This research aims to analyze financial plan at Carimontir. The method used in the study is qualitative analysis. Carimontir's financial plan is prepared by considering the capital requirements and all costs to run the company's business. Risk management is also prepared based on the ISO 31000:2018 standard so that the company can control all risks and ensure that the company's business is competitive and sustainable.